O14 The training effect of a Virtual reality simulator for percutaneous pedicle screw fixation in the lumbar spine. (3rd November 2019) - Charalambous, Alexander; Segaren, Neil; Haldar, Anil; Aftab, Syed; Lee, Joshua; Akhtar, Kashif
Abstract : Introduction: Virtual reality (VR) offers a risk free environment for surgical trainees to practice procedures. Recent changes to training, including the introduction of the European Working Time Directive, and increased pressures to fill rota gaps have put even more strain on surgical training. Exposure to specialised procedures such as pedicle screw fixation is often limited to placements within a particular subspecialty and training opportunities are therefore even more limited. Our aim was to assess whether use of a VR simulator of percutaneous guidewire placement would show a training effect. Methods: We recruited twenty-four participants, consisting of medical students, postgraduate doctors and specialty doctors in Orthopaedics and Neurosurgery. They were equally divided into three groups based on previous surgical experience; novice, intermediate or expert. The performance metrics measured were; total score, total time, fluoroscopy use, zone of wire placement, wall violation and final wire depth. Each participant performed the procedure in a set order through both left and right pedicles of lumbar vertebrae, resulting in four sets of data per person. The data was then analysed, using a multi-level linear regression model. Results: Initial analysis showed very little variation in total score, zone of wire placement, wall violation and final wire depth. Analysis of learning effect therefore concentrated on time and fluoroscopy exposure and was performed separately for each group. There was a statistically significant reduction in time taken and fluoroscopy exposure over the four attempts for both novices and intermediates(P<0.001). The novice group showed a marked reduction in time taken with a median time of 390 seconds on the first attempt and 147 in the final attempt. There was no statistically significant improvement between the attempts of the experienced group. Discussion and conclusion: VR simulation should be considered a valuable method of augmenting surgical training in Orthopaedics and Neurosurgery. The improvement shown in the novice and intermediate groups suggests a significant learning effect with practice. As this was only evident in the less experienced groups, it suggests VR training would be most useful for trainees. As expected, the experienced group showed the best results overall. This therefore resulted in little scope for improvement. Exposure to procedures such as percutaneous pedicle screw fixation is limited and can result in serious complications. VR simulation would be especially useful for trainees moving into this subspecialty field for the first time, where a procedure can be attempted without risk to patients.